Reflection on the pedagogical practices of the professor of Research Methodology in Higher Education (Research, Society and Development, 2021)
One of the biggest challenges for Higher Education teachers is to remain self-reflective about pedagogical practices and the role of Continuous Education, recycling and incorporating knowledges, skills and abilities, aligning them with technological and scientific advances. Through a literature review, we could notice that the professional attitude through pedagogical practices, the mastery of knowledge, the exercise of technological updating and scientific knowledge positively influence the teaching-learning process, making it more pleasant and profitable. Based on the above, the aim of this research is to elucidate how the association of the teacher’s knowledge and skills with the pedagogical methods and practices of Higher Education contribute to turning the discipline of Metodologia de Pesquisa (Research Methodology) into an attractive discipline for students.